Analysis of the SWOT matrix as a strategy for implementing the Ap-Th1000 Reactor in Brazil (Brazilian Journal of Radiation Sciences (BJRS), 2024)
This article analyzes the SWOT Matrix for the implementation of the AP-Th1000 reactor with thorium fuel, aiming at a future replacement of the current nuclear reactors that use uranium as fuel by thorium. There was a need for an in-depth study of the national and international literature linked to the Brazilian reality. After that, specific meetings were held to detect all possible situations of the 4 main points of the SWOT matrix. During the sessions, which averaged 1 hour, the authors' industrial and academic expertise was demonstrated in competencies such as creativity, collaboration, effective communication, openness and tolerance, quick thinking, synthesis ability, problem focus, and flexibility during the discussions of over 50 items found in the analysis of the 4 points of the SWOT matrix. Each meeting was divided into three parts. The first part, which would be the Creative phase; and a second part, which would be the Critical phase; and, finally, the third phase, where ideas are filtered for the permanence of those that were better founded and of better acceptance. Then, the aspects listed were classified into 4 categories: Strengths (S), Weaknesses (W), Opportunities (O), and Threats (T). After the classification, a ranking of priorities was made, in descending order of importance, according to the authors, of the weaknesses and threats, neutralization suggestions were made. Finally, the data obtained were analyzed. We concluded through the SWOT analysis, we can observe an expressive amount of benefits of using the AP1000 reactor with MOX of Thorium and Uranium in the development of nuclear energy generation technologies in Brazil.